MANAJEMEN PENCEGAHAN KEJAHATAN BAGI PEGAWAI BP INDONESIA: KEBIJAKAN DEPARTEMEN SEKURITI BP INDONESIA UNTUK MENCEGAH PEGAWAI BP INDONESIA MENJADI KORBAN POTENSIAL - Arimadona Duma (Jurnal Kriminologi Indonesia, 2010)
This bachelor thesis tries to explain policies which have been using by BP Indonesia's Security Department as part of multinational oil company to prevent BP Indonesia's Employees from being victimized. Preventing BP Indonesia's Employees from being victimized enable them to show their best and BP Indonesia can regain benefit. Researcher used qualitative method in order to get an in depth and precise data. In order to get an in depth and current analyzes, participant observation, secondary data search, interviews and assessments had been used by researcher. In depth and collaborative analyzed had been used by researcher according to criminological theories such as security management theory, situational crime prevention and social crime prevention theory. Findings suggest that BP Indonesia Security Department have done their job so well that they don't have to increase their security breach in order to prevent the worst. According to experiences and recommendations from BP Indonesia's employees, technical methods needs to be upgraded for the sake of employees comfort.